Non-HIV talaromycosis: Radiological and clinical analysis. Issue 10 (March 2020) - Li, Xinchun; Hu, Wenqing; Wan, Qi; Lei, Qiang; Sun, Chongpeng; Hou, Zhongjun; Shrestha, Nitesh
Abstract : Abstract: To investigate the characteristics of spiral computed tomography (CT), positron emission tomography–computed tomography (PET/CT) and clinical manifestations of talaromycosis to improve the diagnostic level and deepen its recognition in radiology. Radiological, clinical, and pathological manifestations of 15 patients of non-HIV talaromycosis confirmed by bronchofiberscope lung biopsy and/or abscess puncture fluid culture and/or blood culture and/or sputum culture were analyzed retrospectively. All patients underwent chest CT, among them, six had a brain MRI, and six had a PET/CT scan before treatment. On plain CT scan, there were multiple patches and massive consolidation in 6 patients, multiple patchy consolidations and patchy ground-glass opacities in 3 patients, solitary or multiple nodules and masses in 3 patients, multiple cavities and small nodules in 3 patients. Multiple lymphadenectasis appeared in bilateral hila, mediastinum, and neck in 10 patients. In contrast CT scan, the parenchyma of the lesions had a slight enhancement in 10 patients, moderate enhancement in 3 patients, obvious enhancement in 2 patients. Seven cases had bone destruction and hyperplasia, cranial involvement in 1 patient and liver involvement in 3 patients, respectively. On PET/CT, five patients showed elevated standard uptake value (SUV). The radiological manifestations of non-HIV talaromycosis show multiple consolidations, ground-glass opacities, multiple nodules or masses in bilateral lungs, deep-seated enlarged lymph nodes and bone destruction in multiple systems. The final diagnosis should be based on the culture of talaromycosis.